THE EFFECT OF INTEGRITY, COMPETENCE, INDEPENDENCE, AND ACCOUNTABILITY ON AUDIT QUALITY - Salim, Susanto; Kho, Christian (Graduate Program of Universitas Tarumanagara, 2025)
This study investigates the impact of integrity, competence, independence, and accountability on audit quality, employing primary data collected through a questionnaire survey. The study's respondents, comprising auditors from public accounting firms in DKI Jakarta, were selected using a combination of convenience and snowball sampling methods, resulting in a sample of 40 respondents. Data analysis was conducted using a multiple linear regression model with SPSS version 29 software. The findings reveal that all the variables simultaneously have a significant effect on audit quality, with independence and accountability demonstrating positive and significant impacts when analysed individually. In contrast, integrity and competence do not significantly influence audit quality. In conclusion, this study emphasizes the crucial role of fostering independence and accountability in the audit process, while also calling for further exploration of the nuances surrounding integrity and competence within the auditing context.